Pharmacognostic and preliminary phytochemical investigations on the leaves of Viburnum punctatum Buch.-Ham.ex D.Don - Prabhu K.; Karar P.K.; Ponnudurai K.; Hemalatha S. (My University, 2025)
The genus "Viburnum" includes about 200 species under the family "Caprifoliaceae" (Viburnaceae). There are nearly 17 species in India, especially, in the hill stations at an altitude of more than 1500 m. Scientific information on their pharmacognosy, phytochemistry and pharmacology are very scant. Hence, the current study describes some pharmacognostical and preliminary phytochemical investigations undertaken on the leaves of one of those species namely Viburnum punctatum Buch.-Ham.ex D.Don. The samples for research were collected from Nilgiri hills, Tamil Nadu, India and authentificated by Dr.V.Chelladurai, Ex. Prof, Botany, and then subjected for morphological, microscopical and physicochemical analysis. The parameters from the above were recorded with an objective of drawing an attention on those populations as well as a reference for further scientific investigations.